A Big Fish in a Small Pond: Ability Rank and Human Capital Investment - Benjamin Elsner; Ingo E. Isphording (Institute for the Study of Labor (IZA), 2015)
We study the impact of a student's ordinal rank in a high school cohort on educational attainment several years later. To identify a causal effect, we compare multiple cohorts within the same school, exploiting idiosyncratic variation in cohort composition. We find that a student's ordinal rank significantly affects educational outcomes later in life. If two students with the same ability have a different rank in their respective cohort, the higher-ranked student is significantly more likely to finish high school, attend college, and complete a 4-year college degree. These results suggest that low-ranked students under-invest in their human capital even if they have a high ability compared to most students of the same age. Exploring potential channels, we find that students with a higher rank have higher expectations about their future career, a higher perceived intelligence, and receive more support from their teachers.
Keywords: I21; I23; J24; 330; educational attainment; peer effects; ordinal rank; human capital